2017
DOI: 10.3324/haematol.2017.179341
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids induce differentiation of monocytes towards macrophages that share functional and phenotypical aspects with erythroblastic island macrophages

Abstract: The classical central macrophage found in erythroblastic islands plays an important role in erythroblast differentiation, proliferation and enucleation in the bone marrow. Convenient human in vitro models to facilitate the study of erythroid-macrophage interactions are desired. Recently, we demonstrated that cultured monocytes/macrophages enhance in vitro erythropoiesis by supporting hematopoietic stem and progenitor cell survival. Herein, we describe that these specific macrophages also support erythropoiesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 52 publications
5
82
0
Order By: Relevance
“…16 Here we confirm these findings and show that HLA-DR/DP/DQ loss in Dex-treated patients is independent of disease grade (Figure 6A). Consistent with the fact that the gene for CD163 is glucocorticoid-regulated, 18,22,29 we found that CD163 was expressed on a higher percentage of circulating CD14+ monocytes in Dex-treated low and high-grade glioma patients (Figure 6B). In contrast, we see no change in the frequency of the commonly used MDSC marker CD33 (Figure 6C) or the T cell suppressive marker PD-L1 (Figure 6D), indicating that Dex doesn’t universally suppress surface protein expression, but may have specific targets.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…16 Here we confirm these findings and show that HLA-DR/DP/DQ loss in Dex-treated patients is independent of disease grade (Figure 6A). Consistent with the fact that the gene for CD163 is glucocorticoid-regulated, 18,22,29 we found that CD163 was expressed on a higher percentage of circulating CD14+ monocytes in Dex-treated low and high-grade glioma patients (Figure 6B). In contrast, we see no change in the frequency of the commonly used MDSC marker CD33 (Figure 6C) or the T cell suppressive marker PD-L1 (Figure 6D), indicating that Dex doesn’t universally suppress surface protein expression, but may have specific targets.…”
Section: Resultssupporting
confidence: 84%
“…20-22 A recent study evaluating grades II-IV astrocytomas demonstrates that CD163 mRNA expression increases with increasing grade of astrocytoma, and that CD163+ cells produce IL-10 in the GBM tumor microenvironment. 23 Furthermore, this report suggests that CD163 could be used as a prognostic indicator for grade III astroctyomas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, EM supplemented with cHSA, dHSA, or rHSA showed a significantly increased erythroid expansion potential with limited spontaneous differentiation and a complete absence of non-erythroid cells (Figure 1A and Figure S1A). Of note, PBMC contain primarily T-cells, myeloid cells and B-cells and only on average 0.16% CD34 + HSPC that are capable of differentiating into erythroid cells 17,19 . Therefore, expansion curves using PBMC as a starting material show a drop in expansion between day 0 and day 5, caused by a loss of these non-proliferating immune effector cells 17,18 .…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that enucleated cRBC can be generated starting from adult peripheral blood mononuclear cells (PBMC), a better accessible source than cord blood CD34 + cells and allows adult autologous cRBC 17 . Importantly, the erythroid yield from PBMC is 10-15 fold increased compared to CD34 + cells isolated from a similar amount of PBMC, due to support from CD14 + cells present in PBMC 1719 .…”
Section: Introductionmentioning
confidence: 99%